Pentingnya Pengajaran Dalam Keluarga (Refleksi Teologis Dari Ulangan 6:6-7) - Nubatonis, Geri; Nome, Yoshua; Bambangan, Malik (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2025)
This article discusses the importance of teaching faith in the family through a theological reflection on Deuteronomy 6:6-7. Education in the family is understood as the main foundation for the formation of children's character and spirituality, especially in the midst of modern-day challenges such as globalization, technological advancement, and value pluralism. Deuteronomy 6:6-7 provides a strong theological basis for parents' responsibility to instill God's word repeatedly and consistently in children's daily lives. Through a library research approach, this article examines the historical background of the Israelites, where the teaching of faith was an integral part of patriarchal family life, as well as their challenges in maintaining their faith identity in the midst of foreign cultures. The exegetical explanation of Deuteronomy 6:6-7 shows that the teaching of faith is not just a verbal act, but must be internalized in the real life of parents and children. Verbs such as “teach it again and again” and “talk about it” in the original Hebrew text indicate an intentional, consistent, and diligent effort in faith education. Thus, the teaching of faith is not only done through formal commands, but also through daily conversations, living examples, and the application of godly values in every aspect of family life. Furthermore, this article emphasizes the family as a mediator of God's revelation, where the Christian family functions as a “domestic church” that introduces God's love and truth to the next generation. Parents have a prophetic role in home life, responsible for not only teaching the word cognitively, but also living it out through concrete actions. Faith education in the family should be ongoing, creating a space for open dialogue so that children understand their faith more deeply and relevant to the challenges of the times. The article also elaborates on the continuity of God's covenant, where the teaching of faith aims to maintain people's commitment to God from generation to generation. The inheritance of faith is not just about maintaining traditions, but forming communities that live in faithfulness and love for God. The repetition of the teaching of the word serves as a strategy to strengthen children's faith and identity amidst the threat of foreign cultural influences that contradict the values of the Christian faith. In practice, this article emphasizes that parents should be creative and contextual in teaching methods, such as using Bible stories, family prayer, reading the word together, and engaging in spiritual activities. Thus, faith education at home becomes a dynamic process that touches all dimensions of a child's life, from emotional, social, to spiritual aspects. Overall, this article concludes that faith education in the family is the primary responsibility of parents that must be carried out with high theological awareness, life commitment, and perseverance. Through consistent faith education, the family will be the first and foremost place where children experience, understand, and live the word of God, so that the new generation can grow as individuals with strong faith, divine character, and ready to face the challenges of the times. By making the family the center of faith formation, the continuity of the covenant relationship with God can be maintained in every generation.